(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A Foreign direct investment(FDI) is a controlling ownership in a business enterprise in one country by anentity based in another country. It helps in transferring of financialresources, technology and innovative and improved management techniques alongwith raising productivity. An Indian company may receive Foreign DirectInvestment either through automatic route or government route. The objective ofthis paper tries to study the need of FDI in India, to exhibit the sector-wiseposition of FDI’s in India, to rank the sectors based upon highest FDI inflowsand Share of top investing countries in India’s FDI and problems of FDI inIndia. The results show that Mauritius is the country that has invested highlyin India followed by Singapore, Japan, and USA and so on.